(untitled) (CIPEEX, 2025)
Wildlife trafficking in the Amazon constitutes a serious threat to the biodiversity and integrity of the region’s ecosystems. This work analyzes the impacts of this criminal practice, which involves the illegal capture, transport, and trade of native species, aiming to understand its environmental, social, and economic consequences. The research addresses the routes and methods used in trafficking, the demand for exotic species, and the challenges faced in the enforcement and conservation of Amazonian fauna. The results highlight the need for effective measures to combat trafficking, including the strengthening of public policies, the promotion of awareness campaigns, and the involvement of local communities in the conservation of natural resources.